Embracing Intercultural Trust: Cultivating Non-native Teachers’ Cultural Humility in Iranian Kurdistan - Salimi, Jamal; Azizi, Abdullah; Srisarajivakul, Emily; Sajadi, Seyedeh (International Journal of Multicultural Education, 2025)
In the Iranian educational system, minoritized students often face underrepresentation in formal curricula due to racial, ethnic, and cultural differences. This qualitative study explores perspectives of non-native teachers working in state-funded K-12 schools in Sanandaj, Iranian Kurdistan. Using constructivist grounded theory, semi-structured interviews were conducted with 11 teachers whose cultural and linguistic backgrounds differ from their students. Findings revealed four themes: (1) understanding and embracing cultural differences, (2) intercultural learning, (3) adapting teaching methodologies, and (4) building cultural trust. The study contributes to limited research on cultural humility in Iranian schools and offers insights into multicultural education in non-Western contexts.